The hotspots and publication trends in postoperative delirium: A bibliometric analysis from 2000 to 2020 - Lin, Xiaowan; Cao, Ying; Liu, Xiao; Yu, Kang; Miao, Huihui; Li, Tianzuo (Frontiers in Aging Neuroscience, 2022)
Background：Postoperative delirium (POD) is a common aging-associated postoperative complication that has received increasing attention in the context of the aging global population, and the number of articles published on POD is gradually increasing. This study aimed to quantify the basic information of scholarly publications on POD and identify the most impactful literature, trends, and hotspots in POD research. Methods：We searched articles on POD through the Science Citation Index Expanded databases published from 2000 to 2020. Bibliographic information, including year, country, authorship, type, journal, funding, affiliations, subject areas, and hotspots, was collected for further analysis. Results：A total of 2114 articles on POD from 2000 to 2020 were identified. The highest number of studies (n = 748) were published in the United States, comprising the most total citations (13928), followed by China (n = 278) and Germany (n = 209). Inouye, Sharon K. was the most productive author, with 66 publications on POD. The Journal of the American Geriatrics Society published the highest number of articles (n = 80), with the most total citations (4561) and average (57.01), followed by Anesthesia and Analgesia (n = 52), and the British Journal of Anaesthesia (n = 43). Harvard University was the most productive institute, with the highest H-index (n = 46) and highest degree centrality (n = 191). The top hotspots in the field of POD during this period were “elderly,” “cardiac surgery,” “cognitive impairment,” “hip fracture,” and “intensive care unit.” Conclusions：This study provides an overview of developments in the field of POD over the past 20 years using bibliometric analysis. Overall, research on POD has flourished worldwide. The US has a relatively high academic impact owing to its productive expertise and institutions in this field. Despite much research illustrating the diagnosis and management of POD in clinical practice, more basic research is needed.